PENGARUH LITERASI KEUANGAN, INOVASI PRODUK, DAN HARGA TERHADAP KINERJA KEUANGAN (Studi kasus pada UMKM di Alun-alun Sukoharjo) - Aulia Ridha Ratna Putri; Eko Triyanto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
financial performance of Culinary SMEs in Sukoharjo either partially or simultaneously. This research is a quantitative research. The sampling technique is saturated sampling. The population of this research is Culinary SMEs in Sukoharjo. The sample used was 107 respondents. The analysis technique used is the research instrument test, classical assumption test, f test, t test, and the coefficient of determination. These results show that financial literacy has an effect on financial performance, product innovation has an effect on financial permormance, prices have an effect on financial performance, simultaneously financial literacy, product innovation and price have an effect on financial performance on Culinary MSMEs in Sukoharjo